Effects of intraperitoneally injected selenium and vitamin E in rats anesthetized with halothane - Karakilçik, AZ; Hayat, A; Zerin, M; Çay, M (Urban & Fischer Verlag, 2003)
Halothane, commonly used for anesthetizing humans and animals, is one of the most important volatile anesthetics and may cause the formation of free radicals during its biotransformation. Free radicals may lead to degeneration of Liver cells. Vitamin E and glutathione peroxidase (GSH-Px) containing selenium are two natural antioxidants, and these may protect the cellular Lipid and lipoproteins against oxidative damage caused by free radicals. Therefore, the purposes of the present study were to investigate the probable protective effects of intraperitoneally administered Se and vitamin E on liver enzymes and to determine some other hematological parameters in the halothane anesthesia of rats. All rats were randomly divided into five groups. The first group was used as a control, and physiological saline (0.9%) was intra peritoneally injected into these animals as a placebo. The second group was used as an anesthesia control group and was only anesthetized with halothane for two hours. The third group received intraperitoneally administered Se (Na2SeO3, 0.3 mg/200 g body weight), the fourth group vitamin E (dl-alpha-tocopheryl acetate, 100 mg/kg body weight), and the fifth group a Se plus vitamin E combination (Na2SeO3, 0.3 mg/200 g body weight + dL-alpha-tocopheryl acetate, 100 mg/kg body weight). The activities of aspartate aminotransferase, alanine aminotransferase and alkaline phosphatase, triglycerides, erythrocyte counts, the packet-cell volume, hemoglobin concentrations and neutrophyle rates significantly increased (p < 0.05 to p < 0.01) after halothane anesthesia and returned to near control Levels after Se, vitamin E and Se plus vitamin E injections. The values of cholesterol, total protein, white blood cell counts and lymphocyte rates significantly decreased (p < 0.05 to p < 0.01) in the anesthesia control group. However, the levels of albumin, total bilirubin, creatinine, the mean corpuscular volume, the mean corpuscular hemoglobin, and the mean corpuscular hemoglobin concentration were not statistically influenced. In conclusion, we have determined that halothane anesthesia affected some liver enzymes and some other biochemical and hematological parameters. Se, vitamin E and their combination may prevent the increase of liver enzymes after halothane anesthesia. Based upon these results, Se and vitamin E may play an important role in the indication of hepatic cellular injury produced by halothane.
Keywords: selenium; vitamin E; liver enzymes; halothane; rat